Pengembangan Sistem Informasi Manajemen Aset Laboratorium Berbasis Web di Jurusan Teknik Informatika dan Komputer FT UNM - Fachrul, Achmad; Hasrul Bakri; Jumadi M Parenreng (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This research is a type of Research & Development (R&D) research which aims to develop a Web-Based Laboratory Asset Management Information System in the Department of Informatics and Computer Engineering, test the quality and feasibility of the system based on ISO/IEC 25010 quality standards. This research uses a prototype development model. ISO/IEC 25010 quality standard testing is carried out using 6 aspects of testing, namely Functionality Suitability, Reliability, Performance Efficiency, Usability, Portability and Security. The results of the research resulted in a Web-Based Laboratory Asset Management Information System in the Informatics Engineering Department. The test results include a) testing the functionality suitability of the system can be used properly and functions as a whole; b) reliability testing with a success percentage of 100%; c) performance efficiency testing with grade A values, performance 94%, structure 82% and response time 2.4 seconds; d) usability test obtains very good category; e) portability testing shows the system can run properly; f) security testing results in a level of security at level B.